Características vocais acústicas de homens com voz e laringe normais - Beber, Bárbara Costa (2009)
Based on the acoustic analysis of the voice it is possible to obtain information concerning the glottal source and the vocal filter, once these are characteristics that are peculiar to every individual, and may vary according to age, sex, race and the population. Objective: characterize a group of men with normal voice and larynx in terms of their glottal source characteristics and vocal filter. Materials and methods: The group studied in this research was composed of 25 men, with ages ranging from 20 to 39 years old (average age of 28 years old), who were selected using criteria of inclusion and exclusion: Male subjects, normal larynx, young adult age group (20 to 40 years old) and the acceptance of the of free and clear consent term. The exclusion criteria were medical records of neurological, psychiatric, endocrinologic and gastric diseases, vocal complaints, audibly-perceived voice alterations, flu or allergy cases, drinking and smoking habits, previous speech therapeutic and/or otorhinolaryngology treatment, hearing alterations, stomatognathic system alterations, being a singer under 20 years old; or aged over 40 years old. All subjects had the prolonged emission of the vowel [a] recorded and analyzed by the programs Multi Dimensional Voice Program (for the study of the measurements of the glottal source) and Real Time Spectrogram (for the study of the vocal filter), both programs by Kay Elemetrics Corporation®. All the results were statistically analyzed with a significance level of 5% and they were compared to the normality pattern of the program once provided. Results: Concerning the glottal source, the measurements of frequency disturbance and range were the ones that differed the most from the normal patterns, showing high values on the program. About half of the measurements showed normal distribution. About the vocal filter, in the Wide Band Spectrography, there was statistical significance for noise, present in the high frequencies, little definition in the third and the fourth formant, little regularity in the line and medium anti-resonance. In the Narrow Band Spectrography, there was low intensity of the high frequencies and in the entire spectrum, very present noise in the entire spectrum and in the high frequencies, medium noise in the low frequencies, little regularity of the line and medium anti-resonance. Conclusion: It was possible to conclude that the voice of men young adults show acoustic measurements of the glottal source augmented in relation to the value expected by the program used, and great variability of the values among the subjects. Their spectrographs showed large amount of noise in the entire spectrum and in the high frequencies, the third and the fourth formant poorly defined, medium noise in the low frequencies, irregular line, medium anti-resonance, low intensity in the entire spectrum and, in particular, in the high frequencies. This is how it was characterized the group of men young adults with normal voice and larynx in this research, being these conclusions a consequence of the anatomic and physiologic characteristics of their untrained voices.